Exercise stress echocardiography in the identification of coronary artery disease in the elderly with chronotropic incompetence - Sousa, Antônio Carlos Sobral (2007)
FUNDAMENTO: A incompetência cronotrópica (ICT) é freqüente em pacientes idosos e pode limitar o papel do teste ergométrico na identificação da doença arterial coronariana (DAC) nessa população. OBJETIVO: Avaliar o valor da ICT, em uma população idosa, no diagnóstico da DAC. MÉTODOS: Foram estudados 3.308 pacientes, desses, 804 eram idosos (idade >65 anos) que se submeteram a ecocardiografia sob estresse pelo esforço físico (EEEF). Com base na freqüência cardíaca (FC) alcançada durante o teste ergométrico, subdivididos em dois grupos: G1 – 150 pacientes que não atingiram 85% da FC preconizada para a idade e G2 – 654 pacientes que conseguiram atingir. Os grupos foram comparados quanto a características clínicas, índice de contratilidade segmentar do ventrículo esquerdo (IMVE) e cineangiocoronariografia (CACG). RESULTADOS: As características clínicas foram similares entre os grupos. O IMVE foi maior em G1 do que em G2, tanto no repouso (1.09 ± 0.21 versus 1.04 ± 0,15) quanto após esforço (1.15 ± 0.29 versus 1.08 ± 0.2) (p < 0,001). As anormalidades na contratilidade das paredes foram mais freqüentes em G1 do que em G2 (55% versus 37%; p < 0,05), sugerindo que pacientes idosos com ICT apresentam maior freqüência de DAC. Realizou-se CACG em 69% das EEEF positiva para isquemia miocárdica. No G1, 91% dos pacientes com EEEF positivo para isquemia realmente eram portadores doença obstrutiva arterial coronariana (>50%) versus 84,5% em G2. CONCLUSÃO: A ICT está associada à maior freqüência de alterações contráteis em população idosa e adiciona valor preditivo positivo à EEEF ao identificar pacientes com DAC obstrutiva. _________________________________________________________________________________________ ABSTRACT: BACKGROUND: Chronotropic incompetence (CTI) is frequent in elderly patients and may limit the role of the exercise test in the identification of coronary artery disease (CAD) in this population. OBJECTIVE: To assess the value of CTI in an elderly population in the diagnosis of CAD. METHODS: A total of 3,308 patients were studied, 804 were elderly individuals (age > 65 years) who underwent exercise stress echocardiography (ESE). Based on the heart rate (HR) reached during the exercise test, were divided into two groups: G1 150 patients who did not reach 85% of the age-predicted HR, and G2 654 patients who did. The groups were compared to clinical characteristics, segmental left ventricular contractility rate (WMSI) and coronary angiography (CAG). RESULTS: Clinical characteristics were similar between the groups. WMSI was higher in G1 than in G2, both at rest (1.09 ± 0.21 versus 1.04 ± 0.15) and after exercise (1.15 ± 0.29 versus 1.08 ± 0.2) (p < 0.001). Abnormalities in wall contractility were more frequent in G1 than in G2 (55% versus 37%; p < 0.05), thus suggesting that elderly with CTI have a higher frequency of CAD. CAG was performed in 69% ESE positive for myocardial ischemia. In the G1 group, 91% of the ESE were true positive versus 84.5% in G2, that is, presence of obstructive coronary artery disease (> 50%). CONCLUSION: CTI is associated with a higher frequency of contractile alterations in the elderly population and adds a positive predictive value to ESE in the identification of patients with obstructive CAD.